Do Medicare Beneficiaries Living With HIV/AIDS Choose Prescription Drug Plans That Minimize Their Total Spending? - Katherine A. Desmond MS; Thomas H. Rice PhD; Arleen A. Leibowitz PhD (SAGE Publishing, 2017)
This article examines whether California Medicare beneficiaries with HIV/AIDS choose Part D prescription drug plans that minimize their expenses. Among beneficiaries without low-income supplementation, we estimate the excess cost, and the insurance policy and beneficiary characteristics responsible, when the lowest cost plan is not chosen. We use a cost calculator developed for this study, and 2010 drug use data on 1453 California Medicare beneficiaries with HIV who were taking antiretroviral medications. Excess spending is defined as the difference between projected total spending (premium and cost sharing) for the beneficiary's current drug regimen in own plan vs spending for the lowest cost alternative plan. Regression analyses related this excess spending to individual and plan characteristics. We find that beneficiaries pay more for Medicare Part D plans with gap coverage and no deductible. Higher premiums for more extensive coverage exceeded savings in deductible and copayment/coinsurance costs. We conclude that many beneficiaries pay for plan features whose costs exceed their benefits.